2012
DOI: 10.1051/mmnp/20127205
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Lie Group Analysis to Mathematical Modelling in Natural Sciences

Abstract: Abstract. Today engineering and science researchers routinely confront problems in mathematical modeling involving solutions techniques for differential equations. Sometimes these solutions can be obtained analytically by numerous traditional ad hoc methods appropriate for integrating particular types of equations. More often, however, the solutions cannot be obtained by these methods, in spite of the fact that, e.g. over 400 types of integrable second-order ordinary differential equations were summarized in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The detailed review of this subject can be found e.g. in [11] and in [4] and here we emphasize that part of the review in the latter references that is essential in the frame of the current work.…”
Section: Preliminaries On Symmetry Groups and Invariant Solutionsmentioning
confidence: 98%
“…The detailed review of this subject can be found e.g. in [11] and in [4] and here we emphasize that part of the review in the latter references that is essential in the frame of the current work.…”
Section: Preliminaries On Symmetry Groups and Invariant Solutionsmentioning
confidence: 98%
“…be the velocity vector, p(x, y, z, t) be the pressure and ρ(x, y, z, t) be the density in the Cartesian coordinates (x, y, z). The starting model describing the large-scale geophysical motions for baroclinic jets that release potential energy in the atmosphere are given by nonlinear model for internal waves under the Boussinesq approximation ( [20], [21], [22], [23]):…”
Section: Mathematical Modelmentioning
confidence: 99%
“…At the first step towards the classification of symmetries of a differential equation-based model involving arbitrary elements, it is essential to find equivalence transformations for this model. Equivalence transformations map the given DE system to another differential equation from the same general class [26, 30]. Lie groups of equivalence transformations can be sought systematically using techniques similar to those used to determine admitted Lie symmetry groups.…”
Section: Introductionmentioning
confidence: 99%